2022
DOI: 10.3390/microorganisms10040739
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Aspergillus fumigatus in Children with Cystic Fibrosis

Abstract: Background. The clinical relevance of Aspergillus fumigatus (Af) in cystic fibrosis (CF) is controversial. The aims of the study were to assess the prevalence of Af disease in our cohort of CF patients and evaluate whether allergic bronchopulmonary aspergillosis (ABPA) and sensitization to Af affected lung function, body mass index (BMI) and exacerbations. Methods. Clinical data and lung function of CF patients aged 6–18 years followed at the CF Centre of Parma (Italy) were recorded. Patients were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Kraemer et al 13 and Fainardi et al 32 demonstrated that pwCF with ABPA had poorer lung function. In our study, there was no difference between the z-scores of FEV1 and FVC values at the end of the first year among clinical Aspergillus phenotypes, most likely due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Kraemer et al 13 and Fainardi et al 32 demonstrated that pwCF with ABPA had poorer lung function. In our study, there was no difference between the z-scores of FEV1 and FVC values at the end of the first year among clinical Aspergillus phenotypes, most likely due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found A. fumigatus sensitization in 26.2% of the studied population, which is lower than the prevalence reported in most published studies. 7,8 This variation in prevalence may be attributed to differences in the sensitivity of various diagnostic methods used for identifying Aspergillus spp. sensitization.…”
Section: Discussionmentioning
confidence: 99%